Biomimetic and biohybrid systems : 5th International Conference, Living Machines 2016, Edinburgh, UK, July 19-22, 2016 : proceedings /: 5th International Conference, Living Machines 2016, Edinburgh, UK, July 19-22, 2016 : proceedings. (2016) - Unknown
No abstract available